Analysis on Time Window of Shared Parking in Hospitals Based on Parking Behaviors. (13th September 2017) - Chen, Qin; He, Peng; Chen, Jun
Abstract : Hospitals are essential components of a city; huge traffic demand is generated and attracted, causing contradiction between parking supply and demand. By sharing parking berths, limited space can serve more demand which is beneficial to alleviating parking problems. Aimed at improving the capacity of shared parking, the paper analyzes four parking groups in typical hospitals, which are medical staff, outpatients, emergency patients, and visiting groups. The parking demand of medical staff is rigid. For outpatients and visiting groups, longer walking distance is acceptable and more attention is paid to parking fee. By contrast, emergency patients can accept shorter walking distance and focus more on convenience due to urgency. Under this circumstance, parking behaviors selection models are established by means of Multinomial Logit Model. On this basis, time value is adopted to calculate the tolerance of alterative parking time. Moreover, this paper explores the variation of time window, under different parking impedance. A case study is conducted and suggests that start and end point of a certain time window can be influenced by external factors.